Digital Fun Book for Teaching English to Children at TPQ Nurunnahdloh Malang - Dwi Fita Heriyawati; Febti Ismiatun; Frida Siswiyanti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service was proposed with the aim of improving foreign language skills, especially at TPQ Nurunnahdloh Madyopuro Village, Kedungkandang District, Malang City. They will receive innovative teaching techniques so that the English learning situation is more enjoyable because students are actively involved in learning. For example is that student’s do not just sit and take notes, but they use gestures and use digital books that are interactive and interesting for children, namely the Digital English Funbook. In addition, students will think and act faster in learning because the material taught by the teacher will be made interesting through Digital fun books. The method used in the training later is the provision of material and practice. The intended provision of material is that the service team provides material to TPQ children regarding English learning materials.